Pengaruh Gaya Kepemimpinan terhadap Kinerja Pegawai Puskesmas Tampojung Pregi Kecamatan Waru yang Dimediasi oleh Motivasi - Agus Setiawan; Rusdiyanto Rusdiyanto; Chamariyah Chamariyah (Universitas 45 Surabaya, 2025)
Based on its approach, this research is included in the type of cross-sectional research. The research sample was 70 respondents. The purpose of this research is 1) To test and analyze the significant influence of leadership style on the performance of Tampojung Pregi Pamekasan Health Center employees. 2) To test and analyze the significant influence of leadership style on employee motivation at the Tampojung Pregi Pamekasan Community Health Center. 3) To test and analyze whether leadership style has a significant indirect effect on the performance of Tampojung Pregi Pamekasan Health Center employees which is mediated by motivation. The results of the research show that: 1) Leadership style has a significant positive effect on the performance of employees at the Tampojung Pregi Public Health Center, Waru District, with an original sample value of 0.225. 2) Leadership style has a significant positive effect on employee motivation at the Tampojung Pregi Public Health Center, Waru District, with an original sample value of 0.390. 3) Indirectly, leadership style has a significant effect on the performance of employees at the Tampojung Pregi Public Health Center, Waru District, which is mediated by motivation with an original sample value of 0.104.